2014
DOI: 10.5582/irdr.2014.01028
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of AGG interruption patterns within nine world populations

Abstract: The CGG trinucleotide repeat within the FMR1 gene is associated with multiple clinical disorders, including fragile X-associated tremor/ataxia syndrome, fragile X-associated primary ovarian insufficiency, and fragile X syndrome. Differences in the distribution and prevalence of CGG repeat length and of AGG interruption patterns have been reported among different populations and ethnicities. In this study we characterized the AGG interruption patterns within 3,065 normal CGG repeat alleles from nine world popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 44 publications
3
25
0
1
Order By: Relevance
“…In the past 10 years, reports have suggested that 35 to 44 CGG, 4,5 35 to 54 CGG, 6 and <28 CGG repeat lengths 7 may be associated with early ovarian aging. It has recently been reported that women who have both alleles with fewer than 23 repeats have an increased odds of having a child with a disability.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 10 years, reports have suggested that 35 to 44 CGG, 4,5 35 to 54 CGG, 6 and <28 CGG repeat lengths 7 may be associated with early ovarian aging. It has recently been reported that women who have both alleles with fewer than 23 repeats have an increased odds of having a child with a disability.…”
Section: Discussionmentioning
confidence: 99%
“…In some diseases, as SCA1 (MIM# 164400), SCA2 (MIM# 183090), fragile-X syndrome (MIM# 300624), myotonic dystrophy type 2 (DM2; MIM# 602668), and Friedrich ataxia (FRDA; MIM# 229300), nonpathogenic alleles are more likely to be interrupted than expanded alleles, whereas in SCA8 (MIM# 608768), SCA10 (MIM# 603516), and DM1 (MIM# 160900) interruptions are more expected in expanded alleles (Braida et al, 2010;Chung et al, 1993;Hu et al, 2017;Imbert et al, 1996;Landrian et al, 2017;Liquori et al, 2003;Maia et al, 2017;Martins et al, 2005;Menon et al, 2013;Montermini et al, 1997;Moseley et al, 2000;Musova et al, 2009;Ramos et al, 2010;Yrigollen et al, 2014;Zuhlke et al, 2002). Depending on the gene, interruptions in the repetitive tract may be randomly positioned, as in ATXN2, ATXN8OS, and ATXN10, or follow a pattern (Chung et al, 1993;Landrian et al, 2017;Yrigollen et al, 2014). In FMR1, AGG interruptions are usually located every nine or 10 CGGs, whereas in ATXN1 interrupted alleles have one to three CAT interruptions in the middle of the allele intercalated with one CAG, following a configuration from (CAG) n CAT (CAG) n to (CAG) n CAT CAG CAT CAG CAT (CAG) n (Chung et al, 1993;Yrigollen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the gene, interruptions in the repetitive tract may be randomly positioned, as in ATXN2, ATXN8OS, and ATXN10, or follow a pattern (Chung et al, 1993;Landrian et al, 2017;Yrigollen et al, 2014). In FMR1, AGG interruptions are usually located every nine or 10 CGGs, whereas in ATXN1 interrupted alleles have one to three CAT interruptions in the middle of the allele intercalated with one CAG, following a configuration from (CAG) n CAT (CAG) n to (CAG) n CAT CAG CAT CAG CAT (CAG) n (Chung et al, 1993;Yrigollen et al, 2014). Repeat interruptions in nonpathogenic alleles stabilize the repeat tract (Choudhry, Mukerji, Srivastava, Jain, & Brahmachari, 2001;Chung et al, 1993;Yrigollen et al, 2012); in expanded alleles at specific loci interruptions may decrease penetrance or delay age-of-onset, as in SCA1 and DM1 (Botta et al, 2017;Matsuyama, Izumi, Kameyama, Kawakami, & Nakamura, 1999;Menon et al, 2013;Zuhlke et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…FMR1 contains a 5′ noncoding CGG repeat region that may expand beyond the normal range and cause fragile X syndrome (FXS) if fully mutated (4200 CGGs) or other fraxopathies (fragile X tremor/ataxia syndrome, FXTAS and fragile X premature ovarian failure, FXPOF) if in the premutation range (55oCGGso200). Full mutations are generally methylated in the promoter region, with the consequent transcriptional silencing and absence of FMRP translation.1 On the basis of repeat size and instability, FMR1 alleles can be designated as normal (stable 5-44 CGGs), intermediate (slightly unstable 45-54 CGGs) and premutated (very unstable 55-200 CGGs, with the risk of expansion to full mutation dependent on the progenitor gender and allele size).2-4 A complex mechanism involving multiple steps seems to be on the origin of de novo FMR1 expansions, reason why this has been under debate for the last decades.5-8 Cis-acting factors such as AGG interspersions in the CGG repeat region are, however, well known important stability elements.9-12 Normal alleles have AGG interruptions usually after every 9 or 10 CGG triplets, 13 whereas in other allele classes, the number of AGGs tends to be progressively lower as the repeat size increases. In approximately 50% of premutated alleles, an AGG interruption is observed, reducing the risk of expansion upon maternal transmission, particularly in alleles with less than 100 CGGs.…”
Section: Introductionmentioning
confidence: 99%
“…In approximately 50% of premutated alleles, an AGG interruption is observed, reducing the risk of expansion upon maternal transmission, particularly in alleles with less than 100 CGGs. [11][12][13][14][15][16] The loss of AGGs occurs in a polarized way at the 3′-end, creating a long pure (CGG)n with higher mutability. 17,18 On the other hand, while analyzing the interspersion pattern of the repeat, an increased instability seems to be correlated with the presence of the first interruption at the tenth triplet, as the configuration (CGG)9AGG (CGG)n is frequently observed in large normal alleles.…”
Section: Introductionmentioning
confidence: 99%